Interactive presentation of schematic diagrams for performance support. - Ricci KE; Griffin TA; Hodak JC (Military Psychology, 2008)
Sixty-seven United States Navy maintainers (55 men and 12 women) representing both the aviation and surface communities participated in an experiment examining the efficacy of a simulation to assist technicians in rapidly understanding a system's state. Participants were assigned to one of three groups based on the technicians' experience and one of two experimental conditions: simulation (SIM) or technical manual (TM). The experimental task consisted of a series of eight questions regarding the condition of the S-3 aircraft's nose wheel steering (NWS) system given a set of initial aircraft conditions. To aid in performance of the experimental task, participants assigned to the TM condition were given a paper copy of the S-3 aircraft's organizational maintenance manual for the NWS system, and participants assigned to the SIM condition were given a laptop computer running a computer-based interactive model of the S-3 NWS system. Results showed that regardless of level of expertise, participants assigned to the SIM condition answered questions significantly faster than participants assigned to the TM condition. Further, technicians experienced in nonaviation maintenance assigned to the SIM condition answered questions significantly more accurately than experienced nonaviation technicians assigned to the TM condition.